A Simulated Walk in Nature: Testing Predictions From the Attention Restoration Theory. Issue 3 (April 2021) - Crossan, Corey; Salmoni, Alan
Attention restoration theory (ART) predicts that top-down processing during everyday activities can cause attentional fatigue and that bottom-up processing that occurs when people experience nature will be restorative. This study exposed participants to three different conditions using a repeated measures design: a control condition during which participants walked on a typical treadmill; a nature condition during which participants walked on the same treadmill, experiencing a simulated nature walk; and a perturbation condition that included the same simulated nature scene but also required top-down processing during the walk. The findings supported ART predictions. As measured by the backward digit span test, top-down processing in a simulated natural environment nullified the restorative effects and the nature condition produced a significant improvement in directed attention performance compared to the control and perturbation conditions after a 10-min walk. These findings offer practical insights to enhance cognitive functioning through simulated natural environments.